PENGARUH MODEL KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP HASIL BELAJAR SISWA PADA TEMA 7 SD NEGERI 85 PAREPARE - Ila Israwaty; Nur Jannah; Nilan Sari (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study examines the influence of the use of the CIRC model of SD 85 Parepare. The formulation of the problem studied is whether there is an influence on the implementation of the CIRC learning model on student learning outcomes in Theme 7 of Togetherness Subtema 4 Learning 1 class II SD Negeri 85 Parepare. This study aims to determine the effect of implementing the CIRC learning model on student learning outcomes in Theme 7 Togetherness Subtema 4 Learning 1 class II SD Negeri 85 Parepare. This study uses a quantitative approach to the type of experimental research and uses Pre-experimental Design in the form of One Group Pretest-Posttest Design. The sampling technique used was purposive sampling with a sample of 20 students. Data collection techniques in this study were observation, tests in the form of multiple choices and documentation. Data analysis used descriptive statistical analysis techniques and inferential statistical analysis techniques. The results of hypothesis testing using the Paired Sample T-Test test obtained significance of 0.00 (0.00 <0.05) and the results of the analysis of the value of t obtained by tcount> ttable (12.899> 2.86093) indicate that H0 is rejected and Ha is accepted. This difference can be seen in the average student pre-test and post-test learning outcomes obtained in the experimental class. Based on these results, it can be concluded that the CIRC learning model has an effect on the learning outcomes of SD 85 Parepare students.